PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TABUNGAN TERHADAP TINGKAT KEPUASAN NASABAH PADA BMT AL-YAMAN BERASAN - Habibulloh Habibulloh; Nur Anim Jauhariyah (NATUJA : Jurnal Ekonomi Syariah, 2022)
This study aims to analyze the effect of service quality and savings product quality simultaneously and partially on the level of customer satisfaction at BMT Al-Yaman Berasan. This research uses a quantitative method with an associative approach and data management using multiple linear regression analysis methods. Statistical testing in this study used the t test, F test and R Square. Sampling is done by using accidental sampling technique. In the process of collecting data using several methods, namely observation, questionnaire (questionnaire) and documentation. Data analysis techniques were assisted with SPSS v.16 software for windows 7. The results showed that the quality of service and the quality of savings products simultaneously had a significant effect on the level of customer satisfaction at BMT Al-Yaman Berasan. The results of this study also show partially that the variable service quality does not affect the level of customer satisfaction on BMT Al-Yaman Berasan, it is known that at a value of 1.794 <Ttable 1.985 with a significant value of 0.076. While the variable quality of savings products partially influences the level of customer satisfaction on BMT Al-Yaman Berasan, it is known that the value of Thitung is 7.269> Ttable 1.985 with a significant value of 0,000. The coefficient of determination test results shows that customer satisfaction can be explained by the quality of service and the quality of savings products by 56.9%, while (100% -56.9% = 43.1%) is influenced by other variables not included in this study.